RELIGION AND MALAY-DAYAK IDENTITY RIVALRY IN WEST KALIMANTAN - Yusriadi, Yusriadi; Ruslan, Ismail; Hasriyanti, Nunik; Mustolehudin, Mustolehudin; Shin, Chong (El-HARAKAH (TERAKREDITASI), 2021)
Ethnic rivalry triggers competition among individuals, certain actors, and groups. Often, the competition is due to political factors while religion becomes a structural legitimacy. This paper examined how the rivalry between Malay and Dayak in West Kalimantan affected certain groups’ identity. The data of this paper were obtained through a documentation study by reviewing publications and writings on the issue of rivalry and interviews with some figures in West Kalimantan. The result concluded that the rivalry between Malay and Dayak in West Kalimantan was tight due to political factors. The two equally dominant communities have long competed since the colonial period in West Kalimantan. Today's rivalry has taken place since Indonesia's reformation in 1998 and let both groups maintain their identity, and, in some cases, lead to unclear boundaries. They do not live as neighbors but brothers. However, religion remain an essential factor amid the situation and cause the rivalry stronger.Persaingan etnis memicu persaingan antar individu, aktor tertentu, dan melibatkan kelompok. Seringkali persaingan disebabkan oleh faktor politik, sedangkan agama menjadi legitimasi struktural. Makalah ini berupaya untuk melihat bagaimana persaingan antara Melayu dan Dayak di Kalimantan Barat berimplikasi pada identitas kelompok. Data untuk makalah ini diperoleh melalui studi dokumentasi dengan melihat publikasi dan tulisan tentang isu persaingan, serta wawancara dengan sejumlah tokoh di Kalimantan Barat. Kesimpulannya, persaingan antara Melayu dan Dayak di Kalimantan Barat sangat kuat karena faktor politik. Kedua komunitas yang sama-sama dominan ini telah bersaing sejak jaman penjajahan di Kalimantan Barat. Persaingan saat ini telah terjadi sejak reformasi Indonesia pada tahun 1998. Melalui kompetisi ini, masing-masing etnis Melayu dan Dayak mempertahankan identitasnya, dan dalam beberapa kasus menciptakan batasan yang kabur. Mereka ditempatkan sebagai tetangga, tetapi sebagai saudara. Namun, agama tetap menjadi faktor penting di tengah situasi ini, dan membuat persaingan keduanya semakin kuat.